2021
DOI: 10.21203/rs.3.rs-362238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eating Disorders and the Internet: A Descriptive Cross-Sectional Study Monitoring The Pro Ana Phenomenon in An Italian Sample.

Abstract: Background: The Internet is a significant source of information for adolescents, affecting their life and health. The online Pro Anorexia (Pro Ana) phenomenon is a growing danger. The purpose of this study is to evaluate the presence of the Pro Ana phenomenon in an Italian sample of patients affected by Eating Disorders.Methods: This study is a descriptive cross-sectional analysis that examines two different samples of patients affected by eating disorders at different points in time, in 2017 and 2020. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A recent cross-sectional study conducted in Italy on patients with ED [13] documented that more than 80% of the respondents used Internet daily. From 2017 to 2020, the authors observed a rise of the pro-Ana phenomenon among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent cross-sectional study conducted in Italy on patients with ED [13] documented that more than 80% of the respondents used Internet daily. From 2017 to 2020, the authors observed a rise of the pro-Ana phenomenon among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the absence of previous surveys on TikTok use in the medical literature, we developed an anonymous questionnaire to survey our patients. The questionnaire included items that we drew from the medical literature on the general use of the Internet and of social networking sites among children and adolescents with ED [13,20,35,38]. Two authors (J.P., M.D.R.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations